Management Risk Investment (Case Study: Default on Mudharabah) - Vanni, Kartika Marella (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2025)
Investment is a term that is always related to finance and economics. As the times develop, investment is increasingly adjusting to people's interests. One of them is the development of sharia investment. In investing, it is certainly not always profitable, sometimes experiencing ups and downs to losses. This is the background for the birth of investment risk management, so that later every investment risk that will occur investors can be prepared to take further steps to prevent losses. Meanwhile, the deliberations of both parties contributed. The investment that is risky between the two is mudharabah. This is because if the investment suffers a loss, the bank will be fully responsible for everything. Coupled with other risks that can still occur such as default. The existence of this phenomenon, the author will discuss investment risk management in the case study of default in Mudharabah. Keywords : Investment Risk, Default, Mudharabah .